Modeling the dynamics of banana Xanthomonas wilt transmission incorporating infectious force in both asymptomatic and symptomatic stages - Kweyunga, E.H.; Tumwine, Jackson K.; Karamura, E.B. (Sciencedomain International, 2018)
Despite massive efforts by regional governments and partners in the East and Central African region towards fighting Xanthomonas Wilt of banana, the disease is reported to continue to spread to new areas and resurge in others it had been contained. The use of asymptomatic but infectious plants is hypothesized to play a leading role in the persistence of the disease and it's introduction to new areas. A model for the transmission of BXW by symptomless plants is proposed and analyzed. It incorporates both horizontal and vertical transmission modes and a dual source of inoculum in the force of infection. The basic reproduction number, R0, is obtained and it is found to completely determine the global dynamics of the model. By construction of a suitable Lyapunov function for the second additive compound system, the global stability of the endemic equilibrium is established. Numerical simulation and sensitivity analysis of the basic reproduction number indicate that the disease is mainly driven by parameters involving asymptomatic plants rather than symptomatic ones.